2001
DOI: 10.1002/cbf.932
|View full text |Cite
|
Sign up to set email alerts
|

Interference of MI‐D, a new mesoionic compound, on artificial and native membranes

Abstract: MI-D (4-phenyl-5-(4-nitrocinnamoyl)-1,3,4-thiadiazolium-2-phenylamine chloride), a new mesoionic compound, decreased the rate of swelling induced by valinomycin-K+, as well as induced swelling in the presence of nigericin-K+. Shrinkage was also affected, suggesting interference with the inner mitochondrial membrane, which would affect both fluidity and elasticity. Fluorescence polarization of DPH and DPH-PA, probing the core and outer regions respectively, of the DMPC and native membranes, indicated that MI-D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Different classes of mesoionic compounds have demonstrated a wide range of biological activities such as anti-inflammatory and analgesic, 5 antiparasitic, 6,7 antibacterial, 8,9 antiplatelet, fibrinolytic, thrombolytic and broncholytic effects, 10 as well as anticancer potency. [11][12][13][14][15][16][17] The promising therapeutic applications have led us to study these interesting compounds in our laboratory. We have previously described the survival enhancement of Ehrlich and Sarcoma 180 tumor-bearing mice treated with 4-phenyl-5-(4'-X-styryl)-1,3,5-thiadiazolium-2-phenylamine chlorides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different classes of mesoionic compounds have demonstrated a wide range of biological activities such as anti-inflammatory and analgesic, 5 antiparasitic, 6,7 antibacterial, 8,9 antiplatelet, fibrinolytic, thrombolytic and broncholytic effects, 10 as well as anticancer potency. [11][12][13][14][15][16][17] The promising therapeutic applications have led us to study these interesting compounds in our laboratory. We have previously described the survival enhancement of Ehrlich and Sarcoma 180 tumor-bearing mice treated with 4-phenyl-5-(4'-X-styryl)-1,3,5-thiadiazolium-2-phenylamine chlorides.…”
Section: Introductionmentioning
confidence: 99%
“…12 Respiratory chain inhibition, transmembrane potential collapse, and ATPase activity in intact rat liver mitochondria were observed when the 4-phenyl-5-(4'-X-styryl)-1,3,5-thiadiazolium-2-phenylamine chlorides were used. 13,14 In addition, Senff-Ribeiro et al 15 showed that 4-phenyl-5-(4'-nitro-styryl)-1,3,5-thiadiazolium-2-phenylamine chloride displays an important antitumor activity against murine melanoma B16F10. This compound was cytotoxic in vitro, decreasing cell viability and proliferation, and was able to inhibit tumor growth by ca.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, previous studies (16,50) showed that structural characteristics of mesoionic compounds enable them to cross cellular membranes and can strongly interact with biomolecules (2). Thus we can hypothesize that the relaxation induced by CMMTT may probably due to a direct intracellular effect on the endothelial NOS and consequent activation of the NO cascade; nevertheless, additional experiments are necessary to clearly elucidate the action mechanisms involved in this response.…”
Section: Discussionmentioning
confidence: 99%
“…Dimyristoylphosphatidylcholine (DMPC) membranes were prepared as described by AntunesMadeira & Madeira (1984) and Cadena et al (2001). Native mitochondrial membranes were prepared as described by Antunes-Madeira & Madeira (1989).…”
Section: Preparation Of Membranesmentioning
confidence: 99%